ANALISIS LONGITUDINAL DINAMIKA RASIO MURID-GURU DAN IMPLIKASINYA TERHADAP KUALITAS PENDIDIKAN DASAR - Koyyimah, Dinul; Koyyimah, Sulhan (STIT Al-Ibrohimy Bangkalan, 2024)
The student-teacher ratio is an important indicator in assessing the quality and equity of the Islamic Religious Education (PAI) system, but its dynamics in marginalized areas such as Sampang District are still poorly understood. This study aims to analyze the temporal dynamics of the Islamic Religious Education (PAI) student-teacher ratio in Sampang District from 2019 to 2024 and its implications for educational equity. Using a longitudinal design with secondary data analysis, this study examined student-teacher ratio data from all primary schools in Sampang district. The results show significant fluctuations in the student-teacher ratio (from 16.8 in 2019 to 15.2 in 2021, then increasing to 17.5 in 2024), high variability between sub-districts, and mixed temporal correlations. These findings indicate challenges in the consistency of education resource allocation and potential inequalities in education access between sub-districts. The implication is that a more flexible and localized approach to education resource management is needed to improve education equity and quality in Sampang district